Improving The Performance of Alumni Achievement Assessment by Integrating Website-Based Tracer Study Information Systems and Telegram API - Sucipto, Sucipto; Dewi, Ervin Kusuma; Resti, Nalsa Cintya; Santi, Indyah Hartami (TEKNIK, 2020)
It is the mission of Vocational High School (SMK) education in Indonesia to produce highly competitive and skilled graduates. One standard for evaluating the success of vocational education is assessing the achievements of alumni. The evaluation process can be carried out with programmed alumni tracking activities or commonly known as tracer studies. However, the implementations of tracer studies that have been carried out by vocational schools in Kediri are still using the manual method. These conditions make the school find many obstacles in the implementation of tracer studies. Some schools have used technology with e-mail applications but have financial constraints. This research aims to improve the performance of assessing the alumni achievement of Vocational Schools in Kediri by integrating the website-based tracer study information system with social media Telegram API. Usability testing that gave 4.83 of 5 scales has shown that the integration can improve the performance and benefits of an application compared to the application before integration